Facile synthesis of Ag/AgCI/BiOCI composite Z-scheme photocatalyst for visible-light-driven pollutant removal - Chirwa, Evans M.N. (University of Pretoria, 2021)
Dissertation (MEng)--University of Pretoria, 2019.